Modo 201 signature courseware - Ablan, Dan.; Safari eBooks ([S.l.] : AGA Digital Studios : 3D Garage.com, 2006)
"Through complete, start to finish projects, you'll learn how to model, texture, light, and render in this awesome software package. In 18 hours of high-quality video training, learn how to to navigate the amazingly powerful interface, improve workflow, and discover the tools that will help you create and render amazing images, all in modo 203."--Resource description page.
Title from title frames.
Keywords: Luxology modo (Computer file); Computer animation; Computer graphics; Three-dimensional display systems; Electronic books